2022
DOI: 10.3389/fchem.2022.858323
|View full text |Cite
|
Sign up to set email alerts
|

Carbon quantum dots: An environmentally friendly and valued approach to sludge disposal

Abstract: Sewage sludge, produced daily and inherent to urban development, presents problems of disposal that are still challenging today. Its disposal still offers palliative solutions, where the final destination is generally in landfills or, restrictively, to use in agriculture. The synthesis of carbon quantum dots (CQDs) from sewage sludge is a better alternative to use the stock of organic material present in the sludge. The present work aims to produce Carbon quantum dots (CQDs) using principles of green chemistry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…From the FTIR analysis shown in Figure 12 , the absence of a broad band between 3000 and 3500 cm −1 indicates the absence of OH groups and the full polycondensation of Si-OH to the Si-O-Si network. The character of the asymmetric stretching mode vibration of the Si-O-Si group was observed as a doublet at intense peaks in the range of 1091–1073 cm −1 , confirming the formation of network Si-O-Si [ 12 , 13 , 14 ]. From the PAI signature, the amide C=O region is observed around 1710 cm −1 and, at 1774 cm −1 , the absorbance is associated with the imide carbonyl band, and the absorption band for symmetric stretching of C-N was observed at 1385–1363 cm −1 .…”
Section: Resultsmentioning
confidence: 90%
“…From the FTIR analysis shown in Figure 12 , the absence of a broad band between 3000 and 3500 cm −1 indicates the absence of OH groups and the full polycondensation of Si-OH to the Si-O-Si network. The character of the asymmetric stretching mode vibration of the Si-O-Si group was observed as a doublet at intense peaks in the range of 1091–1073 cm −1 , confirming the formation of network Si-O-Si [ 12 , 13 , 14 ]. From the PAI signature, the amide C=O region is observed around 1710 cm −1 and, at 1774 cm −1 , the absorbance is associated with the imide carbonyl band, and the absorption band for symmetric stretching of C-N was observed at 1385–1363 cm −1 .…”
Section: Resultsmentioning
confidence: 90%
“….78 and 26.59%, respectively, was due to depolymerization and the combustion process [3]. The Ea for the first split step (i.e., 19.49 and 19.34 kJ mol −1 ) was higher than the second split step for the second decomposition step (i.e., 18.00 and 18.47 kJ mol −1 ), so it is suggested that the first split step is related to carbon core burn of CQDs (ML≈13.29 and 1.78%) [31]. At the same time, the CS/B QDs decomposition curves revealed three decomposition steps.…”
Section: Fluorescence Microscopymentioning
confidence: 95%
“…The second main decomposition step was split between 266.27-357.27 and 357.40-978.72, and 277.83-361.05 and 362.71-979.81 • C, with a maximum of 331.02 and 397.27, and 330.05 and 400.36 • C, respectively, and ML% of 13.29 and 25.86, and 10.78 and 26.59%, respectively, was due to depolymerization and the combustion process[3]. The Ea for the first split step (i.e.,19.49 and 19.34 kJ mol −1 ) was higher than the second split step for the second decomposition step (i.e., 18.00 and 18.47 kJ mol −1 ), so it is suggested that the first split step is related to carbon core burn of CQDs (ML≈13.29 and 1.78%)[31]. At the same time, the CS/B QDs decomposition curves revealed three decomposition steps.…”
mentioning
confidence: 88%